A degrading heterogeneous microgel assembly scaffold and a method of making the same

CN117801323BActive Publication Date: 2026-10-13SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410006281.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2026-10-13
Estimated Expiration
2044-01-03

AI Technical Summary

Technical Problem

[0003]水凝胶由于其高含水量、良好的粘弹性和生物相容性被广泛使用,但由于其为纳米孔结构,难以为细胞聚集提供足够的空间

Benefits of technology

[0043]本发明利用巯基和降冰片烯之间能够在光引发剂存在下通过紫外光照发生硫醇-烯点击反应生成的共价键来组装微凝胶支架,反应条件迅速且温和,可以适用于组织工程。同时发明设计了两种降解程度不同的微凝胶,快速降解微凝胶能够进行一个快速的降解在微凝胶组装体支架内产生“巢穴”为细胞聚集成团提供充足的空间并且实现药物的智能控释,慢速降解微凝胶则缓慢降解以匹配细胞外基质的重塑和组织再生的需要。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure HDA0004647303960000011
    Figure HDA0004647303960000011
  • Figure HDA0004647303960000012
    Figure HDA0004647303960000012
Patent Text Reader

Abstract

The application discloses a degradable heterogeneous microgel assembly scaffold and a preparation method thereof, and the preparation method comprises the following steps: preparing fast-degradable microgels by cross-linking through forming Schiff base bonds by using double-modified polymers modified by norbornene and oxidation and polymers modified by adipic acid hexahydropyridine; preparing slow-degradable microgels by cross-linking through forming amide bonds by adding a hydrazide cross-linking agent to norbornene-modified polymers and carboxyl-containing polymers; and adding polymers modified by cysteine hydrochloride containing a photoinitiator as an assembly agent to the two kinds of microgels, uniformly mixing the two kinds of microgels, and then performing ultraviolet light irradiation to obtain the degradable heterogeneous microgel assembly scaffold. The microgel assembly scaffold can be used for drug controlled release and tissue regeneration and repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials and tissue engineering, specifically relating to a degradable heterogeneous microgel assembly scaffold and its preparation method. Background Technology

[0002] Cell migration, cell aggregation, and specific differentiation are key processes in tissue development and regeneration. Cell migration and the promotion of cell differentiation towards specific phenotypes can be regulated by drugs, while cell aggregation requires not only drug induction but also sufficient aggregation space. Intelligent drug-controlled release materials can respond to a series of pathological changes in pH, temperature, ROS, and enzymes during tissue regeneration and repair, thereby altering the drug release rate. This allows different drugs to maintain optimal concentrations at specific stages of tissue repair, precisely regulating cell migration, aggregation, and differentiation. Macroporous scaffold materials possess interconnected microporous structures, facilitating cell infiltration, growth, and substance transport, and providing ample space for cell aggregation. Therefore, constructing material systems with intelligent drug-controlled release capabilities and interconnected microporous structures through molecular and microporous structure design is crucial for achieving tissue regeneration and repair.

[0003] Hydrogels are widely used due to their high water content, good viscoelasticity, and biocompatibility. However, their nanoporous structure makes it difficult to provide sufficient space for cell aggregation. Microgels, as micrometer-sized hydrogel particles, can be endowed with specific functions through different designs of their structural units. Microgels with different properties can be assembled in a bottom-up manner through chemical or physical reactions to form macroscopic heterogeneous scaffolds. Gel networks formed by stable covalent bonds such as amide bonds are unaffected by pathological microenvironments such as pH, temperature, and ROS, and can maintain a relatively stable state for a long time with slow degradation. In contrast, dynamic covalent bonds such as acylhydrazone bonds can respond to changes in physiological environments such as pH, temperature, and enzymes, achieving dynamic bonding / breaking. By rationally utilizing stable and dynamic covalent bonds to regulate the cross-linking network structure of microgels, and thus modulating their degradation performance, it is hoped that microgels with different degradation properties can be assembled in a bottom-up manner to form heterogeneous scaffolds, thereby constructing material systems with intelligent drug controlled-release functions and interconnected microporous structures, promoting the development of tissue regeneration and repair materials.

[0004] To achieve intelligent drug release and interconnected microporous structures, novel degradation-heterogeneous scaffolds need to be designed and developed. These scaffolds can achieve intelligent drug release through their degradation heterogeneity, and the spaces created by the degradation differences can provide space for cell aggregation. Summary of the Invention

[0005] To address the aforementioned technical problems in the prior art, the present invention aims to provide a degradation heterogeneous microgel assembly scaffold and its preparation method. This scaffold utilizes the characteristics of Schiff base reaction and amidation reaction to prepare microgels with different degradation rates, and simultaneously uses thiol-ene click reaction to assemble the two microgels into a degradation heterogeneous scaffold.

[0006] This application provides a method for preparing a degradable heterogeneous microgel assembly scaffold, comprising the following steps:

[0007] 1) A rapidly degradable microgel was prepared by cross-linking material A and material B through the formation of Schiff base bonds, wherein material A is a dual-modified polymer modified by norbornene and oxidative modification, and material B is a polymer modified by adipic acid adihydrazide.

[0008] 2) Slow-degrading microgels were prepared by adding hydrazide crosslinking agent to materials D and E to form amide bonds, wherein material D is a carboxyl-containing polymer modified with norbornene; and material E is a carboxyl-containing polymer.

[0009] 3) After mixing the two microgels mentioned above, add a PBS solution containing material G, a photoinitiator, mix thoroughly, and then irradiate with ultraviolet light to obtain a microgel assembly scaffold; the material G is a polymer modified with cysteine ​​hydrochloride.

[0010] The method for preparing the rapidly degradable microgel is as follows:

[0011] a1. Dissolve material A and material B separately in PBS buffer solution, mix and stir evenly, adjust the pH value of material A solution with alkaline solution so that material A and material B cannot form a gel after mixing, mix the pH-adjusted aqueous solutions of material A and material B evenly to obtain mixed solution C, as dispersed phase 1; in some embodiments, the pH value of material A solution is adjusted to 9-10;

[0012] a2. Dilute emulsifier 1 with petroleum ether and add acetic acid and mix well to obtain continuous phase 1;

[0013] a3. After adding dispersed phase 1 to continuous phase 1, vortex to form microdroplets 1. After vortexing, place the centrifuge tube in ice and wait for the microdroplets to cross-link and form microgels.

[0014] a4. After the microdroplets 1 in step a3 have gelled, add petroleum ether without emulsifier to break the emulsion, wait for the petroleum ether to evaporate naturally, wash with PBS solution, and centrifuge to obtain microgel 1, which is the rapidly degraded microgel.

[0015] The method for preparing the slow-degrading microgel is as follows:

[0016] b1: Dissolve materials D and E together in PBS buffer solution, mix and stir until homogeneous to obtain mixed solution F, add crosslinking agent and catalyst to mixed solution F, stir until homogeneous to obtain dispersed phase 2;

[0017] b2: Dilute the fluorinated oil containing emulsifier 2 with fluorinated oil to form continuous phase 2;

[0018] b3: After adding dispersed phase 2 to continuous phase 2, vortex to form microdroplets 2. After vortexing, place the centrifuge tube in a 37°C water bath and wait for the microdroplets to cross-link and form microgels.

[0019] b4. After the microdroplets 2 in step b3 have gelled, add fluorinated oil without emulsifier to break the emulsion. After the fluorinated oil evaporates naturally, wash with PBS solution and centrifuge to obtain microgel 2, which is the slow-degrading microgel.

[0020] In some embodiments, the crosslinking agent is an acylhydrazine crosslinking agent; preferably, it is adipic acid adipic hydrazine.

[0021] In some embodiments, the polymer materials in materials A, B, D, E, and G are selected from biomedical polymers, preferably at least one of hyaluronic acid and gelatin;

[0022] In some embodiments, the concentrations of material A and material B in the dispersed phase in step a1 are 2-4 wt% and 1.5-3.5 wt%, respectively; and the concentrations of material D and material E in the dispersed phase in step b1 are 3-4 wt% and 6-8 wt%, respectively.

[0023] In some embodiments, the mixed solution C, i.e., the dispersed phase 1, described in step a1 is obtained by mixing aqueous solutions of material A and material B in a 1:1 ratio;

[0024] In some embodiments, the preparation of material A in step a1 includes the following steps:

[0025] To a 0.6-0.7 wt% aqueous solution of a polymer material with a molecular weight of 100 kDa, Dowex 50W proton exchange resin was added (the mass ratio of polymer material to Dowex 50W proton exchange resin was 1:3). The mixture was stirred for 5 hours, filtered, and the filtrate was titrated with TBA-OH until the pH was neutral. The filtrate was then freeze-dried to obtain the TBA-modified polymer material. The freeze-dried TBA-modified polymer material was dissolved in anhydrous DMSO at a concentration of 1 wt%. Under nitrogen atmosphere, 5-norbornene-2-carboxylic acid (a mixture of endomers and exomers) and 4-dimethylaminopyridine were added sequentially. The molar ratio of carboxylic acid to TBA-modified polymer material is 2.5:1-3.5:1, and the molar ratio of 4-dimethylaminopyridine to TBA-modified polymer material is 1:1-2:1. Then, the solution temperature is raised to 45℃, and di-tert-butyl carbonate is added to the flask in a molar ratio of 0.3:1-0.5:1 using a syringe. After stirring for 15-25 hours under a nitrogen atmosphere, cold water is added to extinguish the reaction. The reaction solution is then lyophilized after dialysis to obtain norbornene-modified polymer material.

[0026] The norbornene-modified polymer material was dissolved in deionized water at a concentration of 0.15-0.4 wt%, and an equal mass of sodium periodate was added. The mixture was stirred for four hours, and then ethylene glycol was added to terminate the reaction for one hour. The reaction solution was dialyzed and then freeze-dried to obtain the norbornene-modified and oxidized polymers.

[0027] In some embodiments, the preparation of material D in step b1 includes the following steps:

[0028] Dowex 50W proton exchange resin (mass ratio of polymer to Dowex 50W proton exchange resin 1:3) was added to an aqueous solution of a polymer material with a molecular weight of 10 kDa at a concentration of 1.5-2.5 wt%. The mixture was stirred for 5 hours, filtered, and the filtrate was titrated with TBA-OH until the pH was neutral. The filtrate was then freeze-dried to obtain the TBA-modified polymer material. The freeze-dried TBA-modified polymer material was dissolved in anhydrous DMSO at a concentration of 1 wt%. Under a nitrogen atmosphere, 5-norbornene-2-carboxylic acid (a mixture of endomers and exomers) and 4-dimethylaminopyridine were added sequentially. The molar ratio of 2-carboxylic acid to TBA-modified polymer material was 2.5:1-3.5:1, and the molar ratio of 4-dimethylaminopyridine to TBA-modified polymer material was 1:1-2:1. Then, the solution temperature was raised to 45°C, and di-tert-butyl carbonate was added to the flask in a molar ratio of 0.3:1-0.5:1 using a syringe. After stirring under a nitrogen atmosphere for 15-25 hours, cold water was added to quench the reaction. The reaction solution was then dialyzed and freeze-dried to obtain the norbornene-modified polymer.

[0029] In some embodiments, the preparation of material B in step a1 includes the following steps:

[0030] The polymer material and adipic acid hydrazide were dissolved in deionized water. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) was added in two portions as a catalyst. During the reaction, the pH of the reaction solution was adjusted to acidity with 1 mol / L hydrochloric acid solution. After stirring at room temperature for 2-4 hours, the reaction was dialyzed and then freeze-dried to obtain the polymer material modified with adipic acid hydrazide.

[0031] In some embodiments, the crosslinking agent and catalyst in the mixed solution F described in step b1 are adipic acid adihydrazide and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride, respectively; the proportions of the crosslinking agent and the catalyst are 0.3-0.4 wt% and 6-8 wt%, respectively.

[0032] In some embodiments, the emulsifier 1 in step a2 is a Span series emulsifier; the concentration of the emulsifier 1 in petroleum ether is 4-6 wt%, and the volume concentration of the acetic acid in the continuous phase is 0.017-0.027%.

[0033] In some embodiments, the emulsifier 2 in step b2 is a 2 wt% Fluo-Surf fluorinated oil HFE7500 solution; the emulsifier 2 is diluted tenfold with fluorinated oil.

[0034] In some embodiments, the ratio of dispersed phase 1 to mobile phase 1 in the step is 1:10, and the vortex time is 0.5-1 minute; the ratio of dispersed phase 2 to mobile phase 2 is 1:10, and the vortex time is 1-2 minutes.

[0035] In some embodiments, the microdroplets 1 described in step a3 are placed in an insulated foam box containing ice and left to stand for 1-3 hours to allow the microdroplets to cross-link internally.

[0036] In some embodiments, the microdroplets 2 described in step b3 are placed in a 37°C water bath and left to stand for 1-3 hours to allow for internal cross-linking of the microdroplets.

[0037] In some embodiments, the preparation of material G in step 3) includes the following steps:

[0038] The polymer material was dissolved in deionized water. Cysteine ​​hydrochloride and catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) were added for the first time. During this process, the pH of the reaction solution was adjusted to acidity with 1 mol / L hydrochloric acid solution. After stirring for 15-45 minutes, the above operation was repeated with the addition of cysteine ​​hydrochloride and catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC). After stirring for another 15-45 minutes, the above operation was repeated with the addition of cysteine ​​hydrochloride and catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC). After reacting for 15-45 minutes, the reaction solution was dialyzed and then freeze-dried to obtain the cysteine ​​hydrochloride modified polymer material.

[0039] In some embodiments, the photoinitiator in step 3) is lithium phenyl-2,4,6-trimethylbenzoylphosphonate; the concentration of the photoinitiator in the PBS solution of material G is 0.5-5 mg / ml; and the concentration of the cysteine ​​hydrochloride-modified polymer material in the mixed microgel is 0.2-5%.

[0040] Another object of the present invention is to provide a microgel assembly scaffold for degrading heterogeneity prepared by the preparation method described above.

[0041] Another object of the present invention is to provide the application of the heterogeneous microgel assembly scaffold in controlled drug release and tissue regeneration and repair.

[0042] Compared with the prior art, the present invention has the following characteristics:

[0043] This invention utilizes the covalent bonds formed between thiol groups and norbornene through a thiol-ene click reaction under ultraviolet light in the presence of a photoinitiator to assemble microgel scaffolds. The reaction conditions are rapid and mild, making them suitable for tissue engineering. The invention also designs two types of microgels with different degradation rates: a rapidly degrading microgel that rapidly degrades to create "nests" within the microgel assembly scaffold, providing ample space for cell aggregation and enabling intelligent controlled drug release; and a slowly degrading microgel that degrades gradually to match the needs of extracellular matrix remodeling and tissue regeneration. Attached Figure Description

[0044] Figure 1 This is a diagram illustrating the crosslinking mechanism of the rapidly degrading microgels of this invention;

[0045] Figure 2 This is a diagram illustrating the crosslinking mechanism of the slow-degrading microgel of the present invention;

[0046] Figure 3 This is a schematic diagram illustrating the mechanism of microgel assembly in this invention;

[0047] Figure 4 Optical image of the rapidly degrading microgel prepared in Example 1;

[0048] Figure 5 The particle size distributions of the rapidly degradable microgels prepared in Example 1 are shown in the diagram.

[0049] Figure 6 Optical image of the slow-degrading microgel prepared for Example 2;

[0050] Figure 7 The particle sizes of the slow-degrading microgels prepared in Example 2 are shown in the figures.

[0051] Figure 8 This is an image of the injectable verification specimen of the microgel assembly obtained in Example 3;

[0052] Figure 9 The degradation performance of microgel assemblies with different mixing ratios obtained in Example 4;

[0053] Figure 10 The figure shows the compressive stress-strain curves of microgel assemblies with different mixing ratios obtained in Example 5. Detailed Implementation

[0054] The present invention will now be described in further detail with reference to the accompanying drawings, but the embodiments of the present invention are not limited thereto. All chemical reagents used in the embodiments of this application are commercially available products.

[0055] The mechanism of the preparation method of the microgel assembly of the present invention is as follows: Figure 1 , 2 As shown in Figure 3. Figure 1This diagram illustrates the cross-linking mechanism of the Schiff base reaction that forms rapidly degrading microgels. Figure 2 A crosslinking mechanism diagram for preparing slow-degrading microgels by forming amide bonds. Figure 3 A schematic diagram illustrating the mechanism by which rapidly degrading microgels and slowly degrading microgels assemble into a degradation heterogeneous microgel assembly.

[0056] The preparation of norbornene-modified and oxidically modified dual-modified hyaluronic acid described below includes the following steps:

[0057] Weigh 1g of sodium hyaluronate with a molecular weight of 100 kDa and dissolve it in 150 ml of deionized water. After dissolution, add 3g of Dowex 50W proton exchange resin, stir for 5 hours, and filter through the resin. Titrate the filtrate with TBA-OH to pH 7.03. Freeze-dry the resulting solution to obtain TBA-modified hyaluronic acid. Dissolve 1g of TBA-modified sodium hyaluronate in 100 ml of anhydrous DMSO, and under a nitrogen atmosphere, add 1.0362g of 5-norbornene-2-carboxylic acid (a mixture of endomers and exomers) and 0.3905g of 4-dimethylaminopyridine. Then, raise the solution temperature to 45°C, add 0.2182g of di-tert-butyl carbonate, and continue stirring under a nitrogen atmosphere for 20 hours. After quenching the reaction with cold water, dialyze and freeze-dry the reaction solution to obtain norbornene-modified hyaluronic acid.

[0058] 1 g of norbornene-modified sodium hyaluronate was dissolved in 400 ml of deionized water. After dissolution, 1 g of sodium periodate was added, and the mixture was stirred for 4 hours. Then, 2 ml of ethylene glycol was added, and the mixture was stirred for another hour. The solution was dialyzed against deionized water for 3 days using a 3500 molecular weight dialysis bag. After lyophilization, the resulting solution was dual-modified hyaluronic acid, modified by both norbornene and oxidation.

[0059] The preparation of norbornene-modified hyaluronic acid described below includes the following steps:

[0060] 1 g of sodium hyaluronate with a molecular weight of 10 kDa was dissolved in 150 ml of deionized water. After dissolution, 3 g of Dowex 50W proton exchange resin was added, and the mixture was stirred for 5 hours. The resin was then filtered. The filtrate was titrated with TBA-OH to a pH of 7.03. The resulting solution was freeze-dried to obtain TBA-modified hyaluronic acid. 1 g of TBA-modified sodium hyaluronate was dissolved in 100 ml of anhydrous DMSO. Under nitrogen atmosphere, 1.0362 g of 5-norbornene-2-carboxylic acid (a mixture of endomers and exomers) and 0.3905 g of 4-dimethylaminopyridine were added sequentially. The solution temperature was then raised to 45 °C, and 0.2182 g of di-tert-butyl carbonate was added. The mixture was stirred under nitrogen atmosphere for 20 hours. After quenching the reaction with cold water, the reaction solution was dialyzed and then freeze-dried to obtain norbornene-modified hyaluronic acid.

[0061] The preparation of adipic acid-adipylhydrazide-modified gelatin described below includes the following steps:

[0062] Weigh 1g of gelatin and dissolve it in 100ml of deionized water. After dissolution, add 0.696g of adipic acid hydrazide and adjust the pH of the solution to 4.75 with 1 mol / L hydrochloric acid solution. Then add 0.19g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, maintaining the pH of the solution at 4.75 during the reaction. After stirring for 1 hour, add another 0.19g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, maintaining the pH of the solution at 4.75 during the reaction, and continue stirring for 2 hours. Dialyze the solution with deionized water at pH 3.15 for three days using a dialysis bag with a molecular weight of 8000-12000, and lyophilize to obtain adipic acid hydrazide-modified gelatin.

[0063] The preparation of cysteine ​​hydrochloride modified gelatin described below includes the following steps:

[0064] Weigh 1g of gelatin and dissolve it in 100ml of deionized water. After dissolution, add 0.2272g of cysteine ​​hydrochloride and 0.3566g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; stir the reaction for half an hour, then add another 0.2272g of cysteine ​​hydrochloride and 0.3566g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; continue stirring the reaction for half an hour, then add the final 0.2272g of cysteine ​​hydrochloride and 0.3566g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. During the entire reaction, adjust the pH of the solution to approximately 4.75 with 0.1 mol / L hydrochloric acid solution; finally, stir the reaction for another half hour, dialyze the reaction solution, and then freeze-dry it to obtain cysteine ​​hydrochloride modified gelatin.

[0065] Example 1

[0066] (1) 60 mg of norbornene-modified and oxidically modified hyaluronic acid, and 50 mg of adipic acid-modified gelatin were added to 1 ml of PBS solution and heated to 50 °C with stirring to dissolve. 60 μL of 1 mol / L sodium hydroxide solution was added to the dissolved oxidically modified hyaluronic acid solution to prevent it from forming a gel when mixed with the adipic acid-modified gelatin.

[0067] (2) Dissolve Span 80 in petroleum ether at a concentration of 5 wt%, and add acetic acid (the volume concentration of acetic acid in petroleum ether in which Span 80 is dissolved is 0.02%) to the petroleum ether in which Span 80 is dissolved, mix them evenly and use them as the oil phase continuous phase.

[0068] (3) The oxidized hyaluronic acid after pH adjustment and the gelatin modified with adipic acid and adipamide were mixed evenly in a ratio of 1:1 to obtain an aqueous dispersion phase.

[0069] (4) Mix the aqueous dispersed phase and the oil continuous phase in a centrifuge tube at a ratio of 1:10. After vortexing for 1 minute, form water-in-oil microdroplets. Place the centrifuge tube after vortexing in a foam box containing ice and let it stand for 2 hours to allow the microdroplets to cross-link and form microgels.

[0070] (5) The cross-linked microgel was washed three times with petroleum ether without Span 80, then fresh petroleum ether was added to break the emulsion. After the petroleum ether evaporated naturally, it was washed with PBS and centrifuged at 2000 r / min for 5 minutes to obtain the microgel.

[0071] This embodiment utilizes dual-modified hyaluronic acid, modified with norbornene and oxidized. The optical image of the microgel prepared in this example is shown below. Figure 4 As shown; the particle size distribution of the microgel prepared in this example is as follows. Figure 5 As shown, the polymer microgels have a narrow particle size distribution, with an average particle size of 80 micrometers.

[0072] Example 2

[0073] (1) 30 mg of norbornene-modified hyaluronic acid (10 kDa) and 60 mg of gelatin were dissolved together in 1 ml of PBS solution, and the solution was heated to 50 °C and stirred to dissolve. 0.003 g of adipic acid adihydrazide and 0.06 g of 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride were added to the solution, and the solution was stirred to dissolve to obtain an aqueous dispersion.

[0074] (2) Dilute the 2% Fluo-Surf 7500 solution tenfold to a concentration of 0.2wt% with fluorinated oil HFE7500 as the oil phase continuous phase;

[0075] (3) Add 1 ml of dispersed phase to 10 ml of oil phase, vortex for 2 minutes to form water-in-oil microdroplets, place the centrifuge tube in a 37°C water bath and let it stand for 2 hours to allow the microdroplets to cross-link and form microgels. (4) Demulsify the cross-linked microgels with volatile fluorinated oil HFE7300, wait for the fluorinated oil to evaporate naturally, wash with PBS, and centrifuge at 2000 r / min for 5 minutes to obtain slow-degrading microgels.

[0076] The optical image of the slowly degrading microgel prepared in this example is shown below. Figure 6 As shown; the particle size distribution of the slow-degrading microgel prepared in this example is shown in the figure. Figure 7 As shown, the polymer microgels have a narrow particle size distribution, with an average particle size of 120 micrometers.

[0077] Example 3

[0078] 20 mg of cysteine ​​hydrochloride-modified gelatin was dissolved in 1 ml of PBS solution, and 1.5 mg of photoinitiator phenyl-2,4,6-trimethylbenzoylphosphonate lithium was added and stirred evenly as an assembly agent. The rapidly degrading microgel and the slowly degrading microgel were mixed at a volume ratio of 1:2. The assembly agent was added to the mixed microgel at a rate of 100 μL / mL. After irradiation with ultraviolet light for 30 s, the microgel assembly scaffold was obtained.

[0079] The injectability of the microgel assembly scaffold prepared in this embodiment is as follows: Figure 8 As shown, the microgel can be extruded into the mold using a syringe, and then cross-linked with ultraviolet light to form an assembly scaffold. After the mold is removed, it can effectively maintain its original shape and has good injectability.

[0080] Example 4

[0081] 20 mg of cysteine ​​hydrochloride-modified gelatin was dissolved in 1 ml of PBS solution, and 1.5 mg of photoinitiator phenyl-2,4,6-trimethylbenzoylphosphonate lithium was added and stirred until homogeneous as an assembly agent. Rapidly degrading microgels and slowly degrading microgels were mixed at volume ratios of 1:1 and 1:2, respectively. The assembly agent was then added to the mixed microgels at a rate of 100 μL / mL. After irradiation with UV light for 30 s, a microgel scaffold assembly was obtained. 200 μL of the microgel assembly was immersed in serum-free basal culture medium, and its swelling rate was measured to observe its degradation changes.

[0082] The degradation performance of the microgel assembly prepared in this example is as follows: Figure 9 As shown in the experimental results, for microgel assemblies with a ratio of 1:1 and 1:2 for both rapid and slow degradation microgels, the rapid degradation microgels were degraded within 7 days.

[0083] Example 5

[0084] 20 mg of cysteine ​​hydrochloride-modified gelatin was dissolved in 1 ml of PBS solution, and 1.5 mg of photoinitiator phenyl-2,4,6-trimethylbenzoylphosphonate lithium was added and stirred until homogeneous as the assembly agent. Rapidly degrading microgels and slowly degrading microgels were mixed at volume ratios of 1:1 and 1:2, respectively. The assembly agent was then added to the mixed microgels at a rate of 100 μL / mL. After irradiation with UV light for 30 s, the microgel assembly scaffold was obtained. 200 μL of the microgel assembly was immersed in serum-free basal culture medium. Samples were collected at different time points, and the compressive modulus values ​​of different groups of microgel assemblies at different time points were measured using a dynamic mechanical analyzer.

[0085] The compressive stress-strain curves of microgel assemblies with different proportions prepared in this example are shown below. Figure 10 As shown, a 1:1 ratio can be observed. Figure 10 The mechanical properties of the ratio of a) gradually decrease with the extension of degradation time, while the mechanical properties of 1:2 ( Figure 10 b) The proportion of the slow-degrading microgels maintains constant mechanical properties, mainly because the increased proportion of the slow-degrading microgels improves the stability of the assembly structure and provides good mechanical support.

Claims

1. A method for preparing a degradable heterogeneous microgel assembly scaffold, characterized in that, Includes the following steps: 1) Rapidly degradable microgels were prepared by crosslinking materials A and B through the formation of Schiff base bonds, wherein material A is a dual-modified polymer of norbornene and oxidative modification, and material B is a polymer modified with adipic acid adipylhydrazide; material A has the structure shown in the figure below: 2) Slow-degrading microgels were prepared by adding hydrazide crosslinking agent to materials D and E to form amide bonds. Material D is a carboxyl-containing polymer modified with norbornene; material E is a carboxyl-containing polymer. 3) After mixing the two microgels mentioned above, add a PBS solution containing material G, a photoinitiator, mix thoroughly, and then irradiate with ultraviolet light to obtain a microgel assembly scaffold; the material G is a polymer modified with cysteine ​​hydrochloride. Among them, the polymer material in materials A, B, D, E and G is at least one of hyaluronic acid and gelatin.

2. The preparation method according to claim 1, characterized in that, The method for preparing the rapidly degrading microgel in step 1) is as follows: a1: Dissolve material A and material B separately in PBS buffer solution, mix and stir evenly, adjust the pH value of material A solution with alkaline solution so that material A and material B cannot form a gel after mixing, mix the pH adjusted material A solution with material B solution evenly to obtain mixed solution C, as dispersed phase 1; a2. Dilute emulsifier 1 with petroleum ether and add acetic acid and mix well to obtain continuous phase 1; a3. After adding dispersed phase 1 to continuous phase 1, vortex to form microdroplets 1. After vortexing, place the centrifuge tube in ice and wait for the microdroplets to cross-link and form microgels. a4. After the microdroplets 1 in step a3 have gelled, add petroleum ether without emulsifier to break the emulsion, wait for the petroleum ether to evaporate naturally, wash with PBS solution, and centrifuge to obtain rapidly degraded microgels; The method for preparing the slow-degrading microgel in step 2) is as follows: b1: Dissolve materials D and E together in PBS buffer solution, mix and stir until homogeneous to obtain mixed solution F, add hydrazide crosslinking agent and catalyst to mixed solution F, and stir until homogeneous to obtain dispersed phase 2; b2: Use fluorinated oil containing emulsifier 2 as continuous phase 2; b3: After adding dispersed phase 2 to continuous phase 2, vortex to form microdroplets 2. After vortexing, place the centrifuge tube in a 37°C water bath and wait for the microdroplets to cross-link and form microgels. b4. After the microdroplets in step b3 have gelled, add fluorinated oil without emulsifier to break the emulsion. After the fluorinated oil evaporates naturally, wash with PBS solution and centrifuge to obtain a slowly degrading microgel.

3. The preparation method according to claim 2, characterized in that, The concentrations of material A and material B in dispersed phase 1, as described in step a1, are 2-4 wt% and 1.5-3.5 wt%, respectively. The concentrations of materials D and E in dispersed phase 2 in step b1 are 3-4 wt% and 6-8 wt%, respectively.

4. The preparation method according to claim 2, characterized in that, The mixed solution C mentioned in step a1, i.e., dispersed phase 1, is obtained by mixing aqueous solutions of material A and material B in a 1:1 ratio.

5. The preparation method according to claim 1 or 2, characterized in that, The preparation of material A includes the following steps: Dowex 50W proton exchange resin was added to an aqueous solution of a polymer material with a molecular weight of 100 kDa at a concentration of 0.6-0.7 wt%. The mass ratio of polymer material to Dowex 50W proton exchange resin was 1:

3. The mixture was stirred and filtered. The filtrate was titrated with TBA-OH until the pH was neutral and then freeze-dried to obtain the TBA-modified polymer material. The TBA-modified polymer material was dissolved in anhydrous DMSO at a concentration of 1-2 wt%. Under a nitrogen atmosphere, 5-norbornene-2-carboxylic acid and 4-dimethylaminopyridine were added sequentially. The molar ratio of 5-norbornene-2-carboxylic acid to TBA-modified polymer material was 2.5:1-3.5:

1. The molar ratio of 4-dimethylaminopyridine to TBA-modified polymer material is 1:1-2:

1. Then, the solution temperature is raised to 45℃, and di-tert-butyl carbonate is added to the flask at a molar ratio of 0.3:1-0.5:

1. After stirring under a nitrogen atmosphere for 15-25 hours, cold water is added to extinguish the reaction. The reaction solution is lyophilized after dialysis to obtain norbornene-modified polymer material. The norbornene-modified polymer material was dissolved in deionized water at a concentration of 0.15-0.4 wt%, and an equal mass of sodium periodate was added. The mixture was stirred and reacted, and then ethylene glycol was added to terminate the reaction. The reaction solution was dialyzed and then freeze-dried to obtain a dual-modified polymer with norbornene modification and oxidation modification.

6. The preparation method according to claim 1 or 2, characterized in that the preparation of material D includes the following steps: Dowex 50W proton exchange resin was added to an aqueous solution of a polymer material with a molecular weight of 10 kDa at a concentration of 1.5-2.5 wt%, with a mass ratio of polymer material to Dowex 50W proton exchange resin of 1:

3. The mixture was stirred, the resin was filtered, and the filtrate was titrated with TBA-OH until the pH was neutral. The filtrate was then freeze-dried to obtain the TBA-modified polymer material. The freeze-dried TBA-modified polymer material was dissolved in anhydrous DMSO at a concentration of 0.5-1.5 wt%. Under a nitrogen atmosphere, 5-norbornene-2-carboxylic acid and 4-dimethylaminopyridine were added sequentially, with a molar ratio of 5-norbornene-2-carboxylic acid to TBA-modified polymer material of 2.5:1-3.5:

1. The molar ratio of 4-dimethylaminopyridine to TBA-modified polymer material was 1:1-2:

1. The solution temperature was then raised to 45°C, and di-tert-butyl carbonate was added to the flask in a molar ratio of 0.3:1-0.5:1 using a syringe. After stirring for 15-25 hours under a nitrogen atmosphere, cold water was added to quench the reaction. The reaction solution was then dialyzed and freeze-dried to obtain the norbornene-modified polymer.

7. The preparation method according to claim 1 or 2, characterized in that, The preparation of material B includes the following steps: The polymer material and adipic acid hydrazide were dissolved in deionized water. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added in two portions as a catalyst. During the reaction, the pH of the reaction solution was adjusted to acidity with hydrochloric acid solution. After stirring at room temperature for 2-4 hours, the reaction was dialyzed and then freeze-dried to obtain the polymer modified with adipic acid hydrazide.

8. The preparation method according to claim 2, characterized in that, The crosslinking agent and catalyst in the mixed solution F described in step b1 are adipic acid adihydrazide and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride, respectively; the proportions of the crosslinking agent and the catalyst in solution F are 0.3-0.4 wt% and 6-8 wt%, respectively.

9. The preparation method according to claim 2, characterized in that, In step a2, the emulsifier 1 is a Span series emulsifier; the concentration of the emulsifier 1 in petroleum ether is 4-6 wt%, and the volume concentration of the acetic acid in the continuous phase is 0.017-0.027%; the emulsifier 2 is a 2 wt% Fluo-Surf fluorinated oil HFE7500 solution; the emulsifier 2 is diluted ten times with fluorinated oil.

10. The preparation method according to claim 2, characterized in that, In step a3, the ratio of dispersed phase 1 to mobile phase 1 is 1:10, and the vortex time is 0.5-1 minute; in step b3, the ratio of dispersed phase 2 to mobile phase 2 is 1:10, and the vortex time is 1-2 minutes.

11. The preparation method according to claim 2, characterized in that, The microdroplet 1 described in step a3 is placed in an insulated foam box containing ice and left to stand for 1-3 hours to allow the microdroplet to crosslink internally; the microdroplet 2 described in step b3 is placed in a 37°C water bath and left to stand for 1-3 hours to allow the microdroplet to crosslink internally.

12. The preparation method according to claim 1, characterized in that, Step 3) The preparation of material G includes the following steps: The polymer material was dissolved in deionized water. Cysteine ​​hydrochloride and catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added for the first time, and the pH of the reaction solution was adjusted to acidity with hydrochloric acid solution during the process. After stirring the reaction, the above operation was repeated to add cysteine ​​hydrochloride and catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride for the second time. After stirring the reaction again, the above operation was repeated to add cysteine ​​hydrochloride and catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride for the third time. After the reaction, the reaction solution was dialyzed and then freeze-dried to obtain the polymer modified with cysteine ​​hydrochloride.

13. The preparation method according to claim 1, characterized in that, Step 3) The photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate; the concentration of the photoinitiator in the PBS solution of material G is 0.5-5 mg / ml; the concentration of the cysteine ​​hydrochloride modified polymer material in the mixed microgel is 0.2-5%.

14. A degradable heterogeneous microgel assembly scaffold prepared by the preparation method according to any one of claims 1-13.

15. The use of the degradable heterogeneous microgel assembly scaffold of claim 14 in the preparation of materials for controlled drug release or materials for tissue regeneration and repair.